2010
DOI: 10.1021/jp104074t
|View full text |Cite
|
Sign up to set email alerts
|

Role of Graphitic Edge Plane Exposure in Carbon Nanostructures for Oxygen Reduction Reaction

Abstract: The role that nanostructure plays in carbon-based oxygen reduction reaction (ORR) catalysts is unclear. In this publication, the role that graphitic edge plane exposure in carbon-based ORR catalysts was examined using two types of nanofibers: one with high edge plane exposure and one with minimal edge plane exposure. These nanofibers were grown, acid oxidized, and then treated with ammonia to incorporate nitrogen. They were characterized using electron microscopy, hydrophobicity imaging, X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(153 citation statements)
references
References 43 publications
8
142
0
3
Order By: Relevance
“…This could be due to the fact that different nitrogen containing functionalities can have different influences on the selectivity for the ORR, as the nature of the active sites for ORR in CN-type catalysts is still controversial (compare for instance refs [75,[77][78][79]). This is in line with these findings of Biddinger and Ozkan [80] and Zhao et al [75], that indicate that the overall nitrogen content is a poor indicator of ORR activity, and only certain types of nitrogen, e.g., on the edges of graphitic sheets promotes the 4-electron process [81,82].…”
supporting
confidence: 89%
“…This could be due to the fact that different nitrogen containing functionalities can have different influences on the selectivity for the ORR, as the nature of the active sites for ORR in CN-type catalysts is still controversial (compare for instance refs [75,[77][78][79]). This is in line with these findings of Biddinger and Ozkan [80] and Zhao et al [75], that indicate that the overall nitrogen content is a poor indicator of ORR activity, and only certain types of nitrogen, e.g., on the edges of graphitic sheets promotes the 4-electron process [81,82].…”
supporting
confidence: 89%
“…Such doping-derived sites and edge-rich holes are expected to act as active sites in the electrocatalytic reactions. [ 12,17,40,44,49 ] The electrocatalytic performance of NGM was fi rst investigated on a rotating disk electrode (RDE) with a mass loading of ≈0.25 mg cm −2 . All potentials are calibrated to a reversible hydrogen electrode (RHE).…”
Section: Communicationmentioning
confidence: 99%
“…Additionally, the surface functional groups, edge dangling bonds, and defective sites in nanocarbon materials also contribute to their electrocatalytic activity. [ 12,17,21,38,39 ] Carbon nanostructures with higher edge exposure for the appropriate incorporation of nitrogen, [ 40 ] especially within the distance of edge effect, [ 12,17 ] are likely to be more active.Recently, it has been demonstrated that even dopant-free nanocarbon can deliver excellent ORR activity, which was attributed to the edge sites. [ 41 ] However, up to now, the exact active sites in nanocarbon materials and their specifi c roles during ORR and OER remain elusive and controversial.…”
mentioning
confidence: 99%
“…Biddinger and Ozkan [676] studied the role of graphitic edge plane exposure in CNSs for ORR. The authors concluded that nanostructure on its own does not improve ORR activity.…”
Section: Electrocatalysis For Low Temperature Fuel Cell Applications mentioning
confidence: 99%